2016
DOI: 10.5194/se-7-367-2016
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating aluminum toxicity in an acid sulfate soil from Peninsular Malaysia by calcium silicate application

Abstract: Abstract. In response to human population increase, the utilization of acid sulfate soils for rice cultivation is one option for increasing production. The main problems associated with such soils are their low pH values and their associated high content of exchangeable Al, which could be detrimental to crop growth. The application of soil amendments is one approach for mitigating this problem, and calcium silicate is an alternative soil amendment that could be used. Therefore, the main objective of this study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Studies have now shown the beneficial effects of CS on the growth and alleviation of biotic and/or abiotic stresses of plants24252627. In the present study, the dry weight of grain amaranths significantly increased and reached a maximum value when CS was added at the rate of 1.65 g/kg (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Studies have now shown the beneficial effects of CS on the growth and alleviation of biotic and/or abiotic stresses of plants24252627. In the present study, the dry weight of grain amaranths significantly increased and reached a maximum value when CS was added at the rate of 1.65 g/kg (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…In acidic soils, Al toxicity to plants and soil infertility are the main limiting factors for crop growth (Adams, 1984;Kochian, 1995;Ulrich and Sumner, 1991;Kidd and Proctor, 2000;Eimil-Fraga et al, 2016;Elisa et al, 2016). Soil acidity directly affects crop growth through acidic reactions and shows indirect effects on crop growth by affecting nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…In acidic soils, Al toxicity to plants and soil infertility are the main limiting factors for crop growth (Adams, 1984;Kochian, 1995;Ulrich and Sumner, 1991;Kidd and Proctor, 2000;Eimil-Fraga et al, 2016;Elisa et al, 2016). Soil acidity directly affects crop growth through acidic reactions and shows indirect effects on crop growth by affecting nutrient availability.…”
Section: Introductionmentioning
confidence: 99%